The Maximization of Digital Marketing and Business Legality in the Development of De Thela Msme in the New Normal Era: Article - Christina Heti Tri Rahmawati; Rubiyatno; Theodorus Sutadi; Florentinus Nugro Hardianto (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose One of the business sectors that has a quite important role for the national economy and has contributed to the absorption of labor and the distribution of development results is Micro, Small and Medium Enterprises (MSMEs). In the new normal era (Adaptation of New Habits) increasing the ability to use digital marketing will be able to help businesses deal with economic pressures, due to the Covid 19 pandemic which has caused a decrease in people's purchasing power where many people have shifted to buying online. In addition, in running a business, it is necessary to have complete documents or business legality. Likewise, De Thela's MSMEs based on observations have problems in terms of their limited ability to use digital marketing and do not yet have business legality. Therefore, assistance is needed to overcome these MSME problems through digital marketing assistance through social media and the importance of having legality in developing a business. Methods – The methods used in the implementation of community service include problem identification, preparation, assistance, monitoring and evaluation of assistance. Result and discussions – This community service activity has yielded results for De Thela's MSMEs including (1) De Thela's MSMEs have created social media content and joined the Shopee Food and Tukoni marketplaces so they can expand product marketing; and (2) UMKM De Thela has business legality by obtaining a Business Identification Number (NIB). Conclusion – The results of this community service activity have implications where it is hoped that digital marketing assistance and business legality will make it easier for De Thela's MSMEs to develop businesses and increase sales and business sustainability, especially in the new normal era.